h - Henes, Mary.; Murray, Brian H.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
This collection reveals the variety of literary forms and visual media through which travel records were conveyed in the long nineteenth century, bringing together a group of leading researchers from a range of disciplines to explore the relationship between travel writing, visual representation and formal innovation.
Keywords: Literature; Literature -- History and criticism; Literature, Modern -- 19th century; Fiction; European literature; British literature; Literature; European Literature; British and Irish Literature; Literary History; Fiction; Nineteenth-Century Literature; Electronic books